Studies on Phyllocnistis citrella Stainton (Lepidoptera Gracillariidae) in a lemon grove of Western Sicily (Bollettino di zoologia agraria e bachicoltura, 2024)
Fram November 1995 to October 1996, a Phyllocnistis citrella Stainton population has been studied with the aim of evaluating its action on different flushes in a lemon grave of Western Sicily, in which water stress is applied to get summer fruits called "verdelli". The highest number of young Citrus Leaf Miner individuals was recorded on leaves 1-3 cm long. 85% of eggs was found on leaves up to 3 cm, whereas 78% of pupae were on leaves > 5 cm. Adults caught by unbaited sticky traps, outlining the population size, reached the maximum of 47.3 ads. per trap in September. The average sex ratio of pupae was 1.1, that of adults caught on traps 1.2. In late autumn and winter CLM, although ali young stages were present, suffers low temperatures, reaching later the minimum population leve! in March and April. During summer and early autumn the main limiting factor is the availability of new vegetation. Spring flush, which represented 44% of new leaf surface of the year, suffered CLM infestation on 14% of leaves, corresponding to 6% of damaged leaf surface, while summer flush following the irrigation breaking the water stress period, developed 53% of new leaf surface of the year, with 70% of infested leaves and 41 % of damaged leaf surface. Sampling founded mainly on percentage of infested new shoots, but also founded on percentage of infested leaves, leads to an overvaluation ofphytophagous population size. On the contrary the number of CLM larvae per leaf allows to estimate the lost leaf surface. Therefore it is suggested to sample CLM population analyzing about one hundred leaves 1-3 cm long, from shoots collected in four different sites per hectare of lemon grave, without taking note of the eggs; this sampling has to be supported by one more sampling on the new flush. In order to fix an economie intervention threshold, linking CLM population to the possible loss of fruit praduction is needed. Parasitization due to Hymenoptera Eulophidae concerned 9.2% of pupae and fourth larval stage; Apotetrastichus postmarginalis (Boucek) e Neochrysocharis formosa (Westw.) were recorded for the first time on Ph. citrella, and Pnigalio agraules (Walk.) was recorded for the first time in Sicily on this host.
Keywords: Phyllocnistis citrella; Citrus lemon; sampling method; spring and summer flush; Eulophidae